Niẓāmī Badāyūnī : yaʻnī savāniḥ ḥayāt Maulānā Niẓāmuddīn Ḥusain Niẓāmī Badāyūnī, bānī-yi akhbār Ẕūlqarnain va Niẓāmī Pres Badāyūn - Kāẓmī, Muḥammad Aḥmad (Niẓāmī Pres, 1949)
Biography of Niẓāmī Badāyūnī, 1872-1947, Urdu author and founder of Nizami Press in Budaun, Uttar Pradesh.